Private and social religious coping on life satisfaction: examining cultural factors among Latinxs - Moreno, Oswaldo (Mental health, religion & culture, 2021)
This study aimed to examine the direct effects of private and social religious coping on perceived life satisfaction. The secondary aim was to investigate whether cultural factors (i.e., enculturation, acculturation, biculturalism) moderate this relationship. A total of 100 Latinx individuals (78% immigrants) completed measures on religious coping, life satisfaction, acculturation, enculturation, and biculturalism. There was a positive direct relationship between both private and social religious coping and life satisfaction. While acculturation, enculturation, and biculturalism did not moderate the relationship between social religious coping and life satisfaction, acculturation, and biculturalism both moderated the relationship between private religious coping and life satisfaction. Specifically, the relationship was strongest when Latinx individuals reported lower levels of acculturation or biculturalism. Clinical and research implications will be discussed for individuals working closely with the Latinx communities.